(In)tangible resources as antecedents of a company's competitive advantage and performance - Toma Cater; Barbara Cater (Journal for East European Management Studies, 2009)
The paper's purpose is to add to the body of knowledge on the antecedents of a company's competitive advantage and performance by developing and testing a conceptual model. By using structural equation modelling the model is tested on a sample of 182 Slovenian companies. The results show that a cost advantage is positively affected by financial resources and customer capital, while a differentiation advantage is positively affected by financial resources and all three components of intellectual capital. In addition, both forms of competitive advantage positively influence a company's performance. The results offer important theoretical implications in fields such as resource-based theory and customer relationship management as well as important practical implications for managers. – – Das Ziel dieses Artikels ist es, unseren Wissensstand über die Einflussfaktoren auf den Wettbewerbsvorteil und den Unternehmenserfolg zu erweitern, indem ein konzeptuelles Modell entwickelt und geprüft wird. Durch die Verwendung der struktuellen Gleichungsmodellierung wird das Modell mit einem Sample von 182 slowenischen Unternehmen geprüft. Die Ergebnisse zeigen, dass ein Kostenvorteil durch finanzielle Mittel und Kundenkapital positiv beeinflusst wird, während ein Differenzierungsvorteil duch finanzielle Mittel und alle drei Komponenten des intellektuellen Kapitals positiv beeinflusst wird. Außerdem haben beide Formen von Wettbewerbsvorteil einen positiven Einfluss auf den Unternehmenserfolg. Die Ergebnisse haben wichtige theoretische Implikationen für Bereiche wie die ressourcenbasierte Theorie und das Kundenbeziehungsmanagement sowie wichtige praktische Implikationen für Führungskräfte.
Keywords: 650; performance; competitive advantage; tangible resources; intangible resources; intellectual capital; structural equation modelling